Proposal of a system of lessons to develop the speaking skill in the 7th grade at Juan Oscar Alvarado Secondary School - Cervera Darias, Dayana; Toledo Ventura, Yasser; Toledo Medero, Pablo (Universidad de Ciencias Pedagógica "Félix Varela", 2011)
The present research was carried out in “Juan Oscar Alvarado” Secondary School. The school selected has a population of 350 students and the group selected as a simple has a registration of 35 students. During the teaching practice many problems were found regarding the teaching of English, but this paper pretends to give a solution to the lack of speaking skill.. A series of reflections and considerations are presented in this research intending to give a solution to the problem under study.

La presente investigación fue llevada a cabo en la Secundaria Básica Juan Oscar Alvarado en Santa Clara . La escuela seleccionada cuenta con una matrícula de 350 estudiantes y el grupo seleccionado como muestra está compuesto por 35 estudiantes. Durante la práctica docente fueron encontrados algunos problemas con la enseñanza del Inglés en especial con la expresión oral. Una serie de reflexiones y consideraciones son presentadas en esta investigación para tratar de dar una solución al problema detectado
Keywords: Secundaria Básica; Expresión Oral; Inglés; Juan Oscar Alvarado; Santa Clara